Filantropia e participação política no movimento do combate ao câncer infanto-juvenil em Sergipe - Sousa, Raquel Santos (2010)
This study aims to understand what drives individuals to engage specifically in mobilizing the fight against childhood cancer in the city of Aracaju, Sergipe, with the field of analysis and research volunteer leaders and not leaders of the Association of Voluntary Service of Oncology Sergipe (AVOSOS) and the Support Group for Children with Cancer of Sergipe (GACC / SE), two institutions that provide social services and which are characterized as philanthropic and nonprofit organizations. The survey sought to identify, through a case study with eighteen participants, the mechanisms and social logics that are related to a type of political engagement. Making use of exploratory research was used to collect and analyze data from a combination of technical case studies designed to investigate the trajectories of social activists and participant observation. The work discussed in the first chapter the history of social practices in Brazil, considering the changes in ways of doing philanthropy and relationship with this new type of political activism. In the second and third chapters are investigated respectively the social characteristics in the various individual agents who conducted the investigation for the cause of cancer, their justifications, meanings and reasons which lead them to invest more intensively in this type of mobilization. The results indicate combinations of variables that involve the political context, elements of family socialization, education, especially religious and the presence of formal and informal social networks. Among the main considerations that we identified that the interest in participating in the mobilization for the cause of cancer, may vary the trajectories and the combination of resources which structure configurations of the political practices of each participant, and the meanings that the engagement will to represent these.